The role of environmental performance to strengthen firm values to financial performance - Pramono, Hadi; Rohman, Abdul (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2023)
Firm value is very closely related to financial performance, which reflects management's achievements in generating profits. For investors, financial performance is an important aspect in determining investment. In addition to financial results, a company's environmental compliance is also important information to attract and influence investors' perceptions, which can add value to the company. Tobin's Q is used to measure the value of the corporate. ROA and ROE measure financial performance, while environmental performance is measured by PROPER. The study results show that ROE positively affects firm value, while ROA has no effect. Environmental performance can strengthen the impact of ROA on firm value, while the relationship between ROE and firm value cannot be strengthened. However, at an alpha level of 0.1, financial results can increase the impact of ROE on firm value.